COVID-19 Sentiment Analysis Dashboard on Tweets and Trending Hashtags - Azman, Azizul Qusyairin (2021)
Coronavirus disease 2019 (COVID-19) outbreak in Malaysia sparks different sentiment on its vaccination program, government policies and the rising number of cases especially in Twitter platform. It is well-known that Twitter has become an increasingly popular social media platform in expressing opinions, sharing interest and discuss the latest news. Thus, sentiment analytics can examine and classify the views from Twitter users to different polarity and categorization.